Sistem Informasi Rekam Medis Berbasis Aplikasi Desktop untuk Daerah Pedesaan - Dwicky Darmawan; Silmi Ath Thahirah Al Azhima; Nurul Fahmi Arief Hakim (Department of Electrical Engineering, UNJANI, 2022)
Rural areas have several challenges that must be resolved. The availability of internet connections in the rural area is also one of the facilities that until now has not been evenly distributed. The clinical administration system is still conventional which has many weaknesses such as data processing, time management, and requires document storage space. So that the conventional system reduces the quality of clinical health services in the area. Therefore, this research was made with the method used is the waterfall model which aims to solve the challenges in making information systems. The advantage of using this method is that it is easy to use, directed, structured, and good for optimization. In this research, the information system created is in the form of a desktop application and is made using the Python programming language and MySQL database as a data storage area. This system is able to store personal data and patient history data according to the required information. In addition, this clinical information system is able to process data quickly and accurately, minimize lost data, search for the required data quickly, make patient data reports quickly and neatly, the system can be accessed by users even though there is no internet signal, and can reduce use of paper and reduce the use of space for patient data document storage.